BUSINESS PROCESS REENGINEERING IN LABUAN FIRE SERVICES OPERATIONS: A CASE STUDY - Amboala, Tamrin; Japang, Minah; Likoh, Jonathan; Yusak, Mohd Yuszreen (Labuan e-Journal of Muamalat and Society (LJMS), 2010)
Most of the Business Processes Reengineering (BPR) researches carried out in private sector because of the dynamism of the business processes. Thus, this case study aim to examine the level of improvement and impact whilst taking into account factors and variables which contribute to success (failure) of business process reengineering (BPR) of e-business project in a small public organization. The project focus to describe experience learned during reengineering process of the operations function at Labuan Fire and Rescue Department (LFRD) with cooperation from Labuan School of Informatics Science (LSIS). The team have eventually proposed an actual interactive design of an e-business system called as regional Fire Department Information System (rFDIS) combined dual functions system: (1) inventory management system that help LFRD inventory officers up-to-date and complete data about its inventory, and (2) is a mapping system specifically for fire hydrant allocation through out the entire Labuan island that emulates the Geographic Information System (GIS).